Perioperative ω-3 Polyunsaturated Fatty Acid Nutritional Support in Gastrointestinal Cancer Surgical Patients: A Systematic Evaluation. (18th May 2016) - Ma, Ying-jie; Liu, Lian; Xiao, Jing; Cao, Bang-wei
ABSTRACT: This study was a systematic evaluation of the beneficial effects of n-3 polyunsaturated fatty acid (PUFA) in abdominal cancer surgical patients. A literature search of the databases PubMed, Medline, Cochrane, and EMBASE was conducted for studies published up to November 2014 in English language journals. Randomized controlled trials (RCTs) examining the effects of n-3 PUFA intake relative to conventional nutrition in surgical patients were included. The main outcomes were the duration of systemic inflammatory response syndrome (SIRS), length of hospital stay (LOS), serum C-reactive protein (CRP) levels, and postoperative complications. We identified 15 RCTs among 158 relevant trials. The results indicated the associations between n-3 PUFA intake and reduced LOS [mean differences (MDs), −2.47 d; 95% confidence intervals (CIs), −3.25 to −1.69], duration of SIRS (MD, −0.57 d; 95% CI, −0.92 to −0.22), and serum CRP levels (MD, −3.97 mg/l; 95% CI, −7.88 to −0.07) compared with consumption of conventional nutrition, as well as reduced incidence of postoperative infectious complications (risk ratio, 0.66; 95% CI, 0.49–0.87). This systematic evaluation suggests that n-3 PUFA significantly reduces the postoperative infectious complication rate, and shortens hospitalization and SIRS duration, particularly in malnourished gastrointestinal cancer patients.